RARE CASE OF IDIOPATHIC GINGIVAL FIBROMATOSIS EFFECTING PRIMARY DENTITION - Ahmed, Sanaa; Ali, Zahid (Journal of Ayub Medical College Abbottabad, 2015)
Gingival fibromatosis (GF) is a rare condition with an estimated incidence of 1:750,000 in autosomal dominant cases and is supposedly genetic in origin. Gingival fibromatosis (GF) may occur as an isolated finding (Idiopathic gingival fibromatosis or IGF) or in combination with additional clinical problems that is, giving rise to syndromic forms of the disease. It usually is triggered when permanent dentition starts to erupt and can cover crowns of the teeth. Gingival fibromatosis occasionally manifests at birth or affect primary dentition. This enlargement may cause mal-position and diastema. Surgical excision of excessive fibrous tissue is the only treatment but it recurs. We are presenting here a case of 5 year old patient presenting with severe idiopathic gingival fibromatosis covering crowns of primary teeth and causing functional impairment.